INVENTARISASI ANGGREK HUTAN DI TAMAN WISATA ALAM BATUPUTIH, KOTA BITUNG, SULAWESI UTARA - Yubu, Amansyo; Pollo, H. N.; Lasut, M. T. (Universitas Sam Ratulangi, 2018)
ABSTRACTÂ Orchid is the largest family that occupies 7-10% of flowering plants and has around 20,000 to 35,000 species. In Sulawesi, according to experts there are around 5000 species of plants that are not known with certainty about their spread and abundance. It has been estimated that approximately 253 endemic orchid species, around 80% of the total number of orchids. In the life stage, tropical orchid plants are epiphytic, with the root system attached to the tree, but does not harm the host tree. There are also those that grow geofitis, with other terms terresterial means to grow on the ground with roots in the soil. There are also those that are saprophytic, grow on the media of dried leaves and weathered wood that has rot into humus. To inventory forest species in Batuputih Nature Park, Bitung City, North Sulawesi. The study was conducted in January - February 2018. Data collection was carried out by exploratory methods. The types of orchids that were found during exploration in TWA Batuputih, which are sorted by the type most found on the three transects: namely Dendrodium sp with a total of 12 points at a height of 40-200 masl, Phaleonopsis amabilis with a height of 52 - 102 masl as many as 3 points while, Dendrodium indivisum with a number of 1 point, which is at an altitude of 136 masl, Nervilia aragoana as many as 10 points with an altitude of 10-84 masl, and Nervilia plicata found only 1 point, at an altitude of 52 masl. Of the five types consisted of 3 genera, namely Dendrodium, Phaleonopsis, and Nervilia, and 2 types of (habitats) terrestrial and epiphytes.Keywords: orchid, type and habitat of forest orchids